Employee Assessment Decision Support System Using the MOORA Method at the National University: Employee Assessment Decision Support System Using the MOORA Method at the National University - Rizki Kurnia; Agung Triayudi; Ben Rahman (Institute of Computer Science (IOCS), 2020)
The quality of human resources is one of the supporting factors to increase the productivity of employee assessment of an agency. So from that high competent human resources can support the existence of employee appraisals, it will be known the achievements achieved by each employee. Decision Support System Application (SPK) was made to assist study programs in employee appraisal. One method of decision support systems is Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) which uses the calculation of criteria weights and the Analytical Hierarchy Process (AHP) method to assess employees. Currently, the National University is still using the manual method in the process of employee performance appraisal by calculating the score of each criterion using Microsoft Excel. The manual assessment process is very likely to occur errors in calculating each criterion and takes a long time in the calculation process. At present, the National University does not yet have a specific application used for employee performance appraisal. Therefore, a decision support system is built using a web-based Multi-Objective Optimization (MOORA) method in order to facilitate the process of evaluating objective employee performance based on weights and assessment criteria that have been determined.